2019
DOI: 10.1111/and.13374
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of red cell distribution width on erectile dysfunction

Abstract: Red cell distribution width (RDW), one of the biomarkers used to measure vascular ageing, is known to correspond with cardiovascular diseases. As coronary artery disease and erectile dysfunction (ED) are both caused by the same shared pathophysiology, in this study, we compared the RDW values of men diagnosed with ED and those of healthy controls. Ninety‐nine patients who were diagnosed with ED were included in the study. The control group consists of 100 men who presented to our outpatient clinic. Patients' f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Fe deficiency can lead to anemia, potentially reducing blood flow to the penis and impeding the ability to achieve an erection. A 2019 study found higher red cell distribution width (RDW) levels in men with erectile dysfunction compared to the control group, suggesting that RDW values may be a useful predictor for identifying and monitoring ED severity [54]. Some studies also propose that severely low testosterone levels are a common finding in cases of severe Fe overload, potentially contributing to erectile dysfunction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Fe deficiency can lead to anemia, potentially reducing blood flow to the penis and impeding the ability to achieve an erection. A 2019 study found higher red cell distribution width (RDW) levels in men with erectile dysfunction compared to the control group, suggesting that RDW values may be a useful predictor for identifying and monitoring ED severity [54]. Some studies also propose that severely low testosterone levels are a common finding in cases of severe Fe overload, potentially contributing to erectile dysfunction [55].…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Red blood cell width distribution (RDW) is an emerging area of interest that may provide insights into the relationship between ED and systemic vascular health. [6][7] Early diagnosis of any underlying medical conditions contributing to ED is crucial for successful treatment. This article explores the intricate connections between ED, HT, and RDW and how these factors interrelate and influence men's health.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 Red cell distribution width (RDW), which may increase due to inflammation, ischemia, and hypoxia, is a measure of the mean corpuscular/erythrocyte volume calculated using the standard deviation of erythrocyte volume heterogeneity. 10,11 Some studies have previously been conducted to evaluate the association of RDW with a poor prognosis in patients with pancreatitis, mostly comparing patients with pancreatitis with patients without pancreatitis. 2,6,9,[12][13][14] The relationship of RDW with mortality was also investigated in patients with acute coronary syndrome, acute appendicitis with inflammation similar to acute pancreatitis, infective diseases such as COVID-19, and malignancies.…”
Section: Introductionmentioning
confidence: 99%